Pengaruh Konsentrasi Inhibitor dari Eceng Gondok dalam Air Hujan dan Air Kran terhadap Laju Korosi: Effect of Water Hyacinth Inhibitor Concentration in Rain Water and Tap Water Media on Corrosion Rate - Emma Hermawati; Yunus Tonapa Sarungu; Bambang Soeswanto; Rispiandi; Alfiana Adhitasari; Sudrajat Harris Abdulloh; Rony Pasonang Sihombing; Retno Indarti (KOVALEN: Jurnal Riset Kimia, 2022)
Organic inhibitors in the corrosion process could be obtained from water hyacinth plant. This plant contained antioxidants such as saponins, which could bind to protective metals from corrosion. The objective of this study was to observe the corrosion rate degradation in rainwater and tap water with saponin content of water hyacinth extract with novelty of using methanol in the maceration process. The sample: methanol ratio used in the maceration process was 1 : 9 (w/v). Steel testing was carried out for 5 days in rainwater and tap water. Based on the test results, the saponin content in the water hyacinth extract could be proven by the stability of the foam produced. The experimental results showed a corrosion rate escalation in tap water samples from 47.7% to 94.5% and samples in rainwater from 11.3% to 52.9% at 75 ppm inhibitor concentration. Based on the research, water hyacinth extract using methanol solvent could be used as a corrosion inhibitor.